How Many People Live with Dementia in Portugal? A Discussion Paper of National Estimates - Manuel Gonçalves-Pereira; Ana Verdelho; Matthew Prina; Maria João Marques; Miguel Xavier (Karger Publishers, 2021)
Dementia poses major public health challenges, and high-quality epidemiological data are needed for service planning. Published estimates of numbers of people with dementia in Portugal have been based, in most cases, on prevalence rates derived from international studies or expert consensus. As in many other countries, Portuguese community prevalence studies' results are nongeneralizable to a country level. Moreover, their prevalence estimates differ (not surprisingly, owing to different methodologies, e.g., design, sampling, and diagnostic criteria). Regardless, the Portuguese 10/66 Dementia Research Group (10/66 DRG) population-based survey fulfilled 10 out of 11 Alzheimer's Disease International quality criteria for prevalence studies. It relied on cross-culturally validated methods, fostering a wide comparability of results. Therefore, we can provide rough estimates of 217,549 community dwellers with dementia in Portugal according to the 10/66 DRG criteria (that would be only 85,162 according to DSM-IV criteria). This refers to people aged 65 years or older who are not institutionalized. Although broadly consistent with international projections, these estimates must be cautiously interpreted. Particularly in the context of scarce funding, which will probably last for years, we need more efficient, evidence-based dementia policies. Concerning further epidemiological studies, high-quality methods are needed but also their comparability potential should be improved at national and international levels. Most of all, fund allocation in Portugal should now privilege routine dementia information systems in both health and social services.